Peruvian Mental Health Reform: A Framework for Scaling-up Mental Health Services - Mauricio Toyama; Humberto Castillo; Jerome T. Galea; Lena R. Brandt; María Mendoza; Vanessa Herrera; Martha Mitrani; Yuri Cutipé; Victoria Cavero; Francisco Diez-Canseco; J. Jaime Miranda (Kerman University of Medical Sciences, 2017)
Background Mental, neurological, and substance (MNS) use disorders are a leading cause of disability worldwide; specifically in Peru, MNS affect 1 in 5 persons. However, the great majority of people suffering from these disorders do not access care, thereby making necessary the improvement of existing conditions including a major rearranging of current health system structures beyond care delivery strategies. This paper reviews and examines recent developments in mental health policies in Peru, presenting an overview of the initiatives currently being introduced and the main implementation challenges they face. Methods Key documents issued by Peruvian governmental entities regarding mental health were reviewed to identify and describe the path that led to the beginning of the reform; how the ongoing reform is taking place; and, the plan and scope for scale-up. Results Since 2004, mental health has gained importance in policies and regulations, resulting in the promotion of a mental health reform within the national healthcare system. These efforts crystallized in 2012 with the passing of Law 29889 which introduced several changes to the delivery of mental healthcare, including a restructuring of mental health service delivery to occur at the primary and secondary care levels and the introduction of supporting services to aid in patient recovery and reintegration into society. In addition, a performance-based budget was approved to guarantee the implementation of these changes. Some of the main challenges faced by this reform are related to the diversity of the implementation settings, eg, isolated rural areas, and the limitations of the existing specialized mental health institutes to substantially grow in parallel to the scaling-up efforts in order to be able to provide training and clinical support to every region of Peru. Conclusion Although the true success of the mental healthcare reform will be determined in the coming years, thus far, Peru has achieved a number of legal, policy and fiscal milestones, thereby presenting a unique and fertile environment for the expansion of mental health services.